Rapid detection of oxacillin-resistant Staphylococcus aureus in blood cultures by an impedance method. - Wu, J J (1997)
The feasibility of using an impedance method for direct detection of oxacillin-resistant Staphylococcus aureus (ORSA) in blood cultures was evaluated. An aliquot (0.1 ml) of the positive blood culture, which showed growth of gram-positive cocci and demonstrated thermonuclease activity, was inoculated into the module well of a Bactometer incubator (bioMerieux Vitek, Hazelwood, Mo.) containing 0.6 ml of Mueller-Hinton agar supplemented with oxacillin (2 microg/ml). The modules were incubated at 37 degrees C, and the change in impedance in each well was continuously monitored by the instrument at 6-min intervals for 24 h. ORSA strains from blood cultures could multiply in the oxacillin-containing medium, and a time point (detection time [DT]) at which an accelerating change of impedance occurred in the medium was obtained, with an average of 5.5 h. The growth of oxacillin-sensitive S. aureus (OSSA) strains was largely inhibited, and no DT was obtained for these strains within an incubation period of 24 h. For 96 positive blood cultures (38 ORSA and 58 OSSA) tested, 36 and 57 were found to be oxacillin resistant and oxacillin sensitive, respectively, by the impedance method. The impedance method had a sensitivity and specificity of 94.7 and 98.3%, respectively, for the detection of ORSA and had an agreement of 96.9% with the disc diffusion method. Comparable results were obtained by the testing of 235 clinical stock cultures of S. aureus (149 ORSA and 86 OSSA). The impedance test is simple for detecting ORSA in blood cultures and may allow proper antimicrobial treatment almost 36 h before the results of the conventional culture methods are available.